Heat Transfer, Volume 2 2004
DOI: 10.1115/imece2004-59859
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Control to Improve Performance of Thermoelectric Coolers

Abstract: Thermoelectric coolers (TECs) have become potential solutions for chip cooling applications. However, the scope of TEC applicability is limited because of poor efficiency that is largely governed by material properties. This low efficiency causes increased heat production resulting in a very narrow band in which the TEC is effective. Since TECs are cooling units composed of numerous individual cooling elements, or thermocouples, the operating efficiency can be improved by implementing distributed control of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Thermoelectric (TE) material has captured extensive interest from the research community to solve the energy crisis and environmental pollution because it can directly and reversely convert heat into electricity. The energy conversion of TE material depends on a dimensionless figure of merit ZT = S 2 σ T /( κ L + κ e ), where S , σ , T , κ L , and κ e represent the Seebeck coefficient, the electrical conductivity, the absolute temperature in Kelvin, the lattice thermal conductivity and the electrical thermal conductivity, respectively. To realize high TE performance, extensive efforts have been devoted to obtaining a high power factor (PF = S 2 σ ) and a low total thermal conductivity (κ tot = κ L + κ e ). In addition to pursuing high TE performance, the efforts should be committed to developing environmentally friendly TE materials considering the increasing environmental pollution around the world.…”
Section: Introductionmentioning
confidence: 99%
“…Thermoelectric (TE) material has captured extensive interest from the research community to solve the energy crisis and environmental pollution because it can directly and reversely convert heat into electricity. The energy conversion of TE material depends on a dimensionless figure of merit ZT = S 2 σ T /( κ L + κ e ), where S , σ , T , κ L , and κ e represent the Seebeck coefficient, the electrical conductivity, the absolute temperature in Kelvin, the lattice thermal conductivity and the electrical thermal conductivity, respectively. To realize high TE performance, extensive efforts have been devoted to obtaining a high power factor (PF = S 2 σ ) and a low total thermal conductivity (κ tot = κ L + κ e ). In addition to pursuing high TE performance, the efforts should be committed to developing environmentally friendly TE materials considering the increasing environmental pollution around the world.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown the potential of increased effectiveness by separately controlling individual thermocouples or groups of thermocouples in TECs [12], [23]. Another major benefit of distributed control is that it may be applied concurrently with other technological advances.…”
Section: Introductionmentioning
confidence: 99%